Pathways From HIV-Related Stigma to Antiretroviral Therapy Measures in the HIV Care Cascade for Women Living With HIV in Canada. (1st February 2018) - Logie, Carmen H.; Lacombe-Duncan, Ashley; Wang, Ying; Kaida, Angela; Conway, Tracey; Webster, Kath; de Pokomandy, Alexandra; Loutfy, Mona R.; Anema, Aranka; Becker, Denise; Brotto, Lori; Carter, Allison; et al.
Abstract : Background: Associations between HIV-related stigma and reduced antiretroviral therapy (ART) adherence are widely established, yet the mechanisms accounting for this relationship are underexplored. There has been less attention to HIV-related stigma and its associations with ART initiation and current ART use. We examined pathways from HIV-related stigma to ART initiation, current ART use, and ART adherence among women living with HIV in Canada. Methods: We used baseline survey data from a national cohort of women living with HIV in Canada (n = 1425). Structural equation modeling using weighted least squares estimation methods was conducted to test the direct effects of HIV-related stigma dimensions (personalized, negative self-image, and public attitudes) on ART initiation, current ART use, and 90% ART adherence, and indirect effects through depression and HIV disclosure concerns, adjusting for sociodemographic factors. Results: In the final model, the direct paths from personalized stigma to ART initiation (β = −0.104, P < 0.05) and current ART use (β = −0.142, P < 0.01), and negative self-image to ART initiation (β = −0.113, P < 0.01) were significant, accounting for the mediation effects of depression and HIV disclosure concerns. Depression mediated the pathways from personalized stigma to ART adherence, and negative self-image to current ART use and ART adherence. Final model fit indices suggest that the model fit the data well [χ 2 (25) = 90.251, P < 0.001; comparative fit index = 0.945; root-mean-square error of approximation = 0.044]. Conclusions: HIV-related stigma is associated with reduced likelihood of ART initiation and current ART use, and suboptimal ART adherence. To optimize the benefit of ART among women living with HIV, interventions should reduce HIV-related stigma and address depression.